Enhancing Self-regulated Learning in Higher Education - Barbara Šteh; Marjeta Šarič (University of Maribor Press, 2020)
A key task of higher education is empowering students for in-depth learning, critical thinking, and assuming responsibility for learning and their future professional work. To attain these goals, it is crucial for students to acquire the ability to regulate their learning. This article presents the concept of self-regulated learning, together with the learning models and factors that contribute to the adequate application of selfregulating strategies. The latter depend on both students' individual characteristics and contextual factors. The processes of self-regulated learning can be learnt and lead students to more meaningful learning, greater satisfaction in studying, and better learning outcomes.